Determination of Employees' Attitudes Concerning Contributing Factors and Early Detection for Prostate Cancer in Baghdad University Colleges in bab-Almudam - Hussein Hadi Atiyah; Haider M. Majeed (Kufa Journal for Nursing Sciences)
Background: Prostate cancer is increasingly becoming one of the most significant health problems facing Iraqi men and the commonest cause of cancer related death in men globally.